Mangrove forest changes using vegetation indices by landsat 8 / Roslina mohamad nawar - mohamad nawar, Roslina (2023)
The status of mangroves nowadays is declining at an alarming rate due to natural disaster threats and anthropogenic factors The lack of information about the current mangrove area especially in Kedah. The exact location and area of the mangrove area are difficult to determine. By using the technologies of remote sensing and geographical information system we can solve this problem and monitor the mangrove forest for time to time. Kedah state forestry can perform restoration and conservation measures towards mangrove forest.